(untitled) (Journal of Foreign Language Studies, 2023)
Writing plays an important role in foreign language learning, especially for undergraduate students who need this skill for academic and research purposes as well as for communication in their future jobs. However, writing is deemed to be the most difficult skill for Vietnamese students. Therefore, a survey was conducted to investigate the factors affecting the English writing skills of non-English majored students at Thang Long University (TLU). 182 first-year students participated in this research by responding to a questionnaire. The survey found that the approach to teaching and assessing writing, teacher instruction and student practice, the influence of sociocultural context, and the writings’ communicative purposes influence students’ writing capability. This study may act as an impetus for future action research, based on which the curriculum for teaching writing to non-English majored students at TLU can be adjusted.